Joining Forces: The Spillover Effects of EPA Enforcement Actions and the Role of Socially Responsible Investors - Dasgupta, Sudipto; Huynh, Thanh D; Xia, Ying (Review of Financial Studies, 2023)
We find that firms reduce toxic emissions at their local plants following EPA enforcement actions against nearby plants operated by peer firms that compete in the same product market. These reductions are more pronounced for plants located near socially responsible mutual funds (SRMFs) that hold these plants’ parent firms’ shares. Close proximity to SRMFs is associated with real investment in abatement measures to mitigate emissions. While plants increase emissions again in the long run, such reversals do not occur in plants located near SRMFs. Taken together, our results suggest that local SRMFs complement EPA enforcement in influencing plants’ emissions. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.